Strategi Pondok Pesantren Attaqwa Bekasi dalam Membentuk Santri yang Berakhlak - Nurazijah, Nurazijah; Rahmawaty, Indira Sabet (Tadbir: Jurnal Manajemen Dakwah, 2023)
The purpose of this study is to find out how the formulation, implementation, and evaluation of Attaqwa Putra Islamic Boarding School is to achieve its goals. The method used is descriptive with qualitative approach so that the author can find out information by describing and describing strategic management at the Attaqwa Putra Islamic Boarding School. Data collection techniques used are observation, interviews and documentation. The results showed the Attaqwa Putra Islamic Boarding School modern Islamic boarding school implements strategic management system in which there strategy formulation process, the formulation carried out by observing from the external and internal environment to determine the program from the vision, mission, goals and set targets. In the implementation process, Attaqwa Putra Islamic Boarding School applies in daily life 24 hours when students run into teachers, classmates, and peers, they must greet, reprimand, and shake hands. And the evaluation applied by the Attaqwa Putra Islamic Boarding School to monitor the activities of the students directly or through the administrators of the Attaqwa Islamic Boarding School.